Criminal Law Policy in Collecting Child Delay According to Law No. 3 Year 1997 - Joharsyah (PT Inovasi Pratama Internasional, 2022)
Juvenile delinquency can no longer be viewed as an ordinary delinquency, many children commit acts that are classified as criminal acts, such as: stealing, carrying sharp weapons, getting into fights, being involved in drug use, and others. So it requires serious attention from the government, parents and the community. Crime cases involving children as perpetrators of crimes bring their own phenomena. Given that children are individuals who are still emotionally unstable and have not become legal subjects, the handling of crime cases with child perpetrators needs special attention. So that the selection of the title of this thesis is Criminal Law Policy in Overcoming Juvenile Delinquency according to Law no. 3 of 1997.